Moderating Effect of Career on Women Online Shopping Behaviour in South-South, Nigeria - Okeke, Titus Chukwuemezie; Omodafe, Philomena Uzezi; Ezeh, Greg Amaechi; Nwatu, Basil Chibuike (Archives of Business Research, 2020)
The study examined the moderating effect of career on women online shopping behaviour. Data for the study were gathered from 330 career women in South-South, Nigeria through structured questionnaire. The study is explored five constructs and evaluated a proposed model explaining the moderating effect of career and the relationship between them. SPSS version 25 was used for preliminary analysis while WarpPLS 7.0 was used in testing the hypothesized relationships. The findings revealed that career moderates the influence of perceived risk, perceived usefulness, performance expectancy and internet self-efficacy in online shopping behaviour among career women while social influence is partially supported and validated from the analysis. The study concludes that the proposed model would serve as a relevant theory that will be helpful in understanding the adoption decisions of career women in working and shopping environments. The study recommends that continuous patronage of online shops by career women can only be guaranteed with improvements in online shopping sites in order to attract and increase traffic to them.